UMPSA drives ethical Artificial Intelligence Initiative - Rohana, Hamzah; Farah Farhani, Wan Zin (UMPSA, 2024)
GAMBANG, 6 December 2024 – Universiti Malaysia Pahang Al-Sultan Abdullah (UMPSA) continues to demonstrate a high commitment to leading the development of science and technology knowledge through the organisation of AI Week, themed ‘To Create Awareness for Responsible AI to the Students and Community’.